2003
DOI: 10.1007/s00125-003-1105-9
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of corneal epithelial wound healing in diabetic rats by the combination of a substance P-derived peptide (FGLM-NH2) and insulin-like growth factor-1

Abstract: Aims/hypothesis. The healing of corneal epithelial wounds is often delayed in individuals with diabetes. The effect of the combination of a substance P-derived tetrapeptide (phenylalanine-glycine-leucinemethionine amide, or FGLM-NH 2 ) and insulin-like growth factor-1 (IGF-1) on corneal epithelial wound healing was investigated in rats with streptozotocininduced diabetes. Methods. The corneal epithelium of diabetic and nondiabetic rats was removed, and the animals were treated by the application of eye drops c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 10 publications
0
43
0
1
Order By: Relevance
“…5 SP enhances the delivery and accumulation of leukocytes, 6 induces interleukin (IL)-8 and IL-6 7e9 expression, and is mitogenic toward smooth muscle cells, fibroblasts, and endothelial cells. 10e12 SP promotes wound healing in nondiabetic and diabetic corneal wounds that mainly involve epithelial cells 13,14 and in nondiabetic cutaneous wounds. 15,16 However, there is little information regarding its effect in diabetic skin wounds that are characterized by chronic inflammation, neuroischemia, and increased expression of MMPs that degrade proteins, including growth factors.…”
mentioning
confidence: 99%
“…5 SP enhances the delivery and accumulation of leukocytes, 6 induces interleukin (IL)-8 and IL-6 7e9 expression, and is mitogenic toward smooth muscle cells, fibroblasts, and endothelial cells. 10e12 SP promotes wound healing in nondiabetic and diabetic corneal wounds that mainly involve epithelial cells 13,14 and in nondiabetic cutaneous wounds. 15,16 However, there is little information regarding its effect in diabetic skin wounds that are characterized by chronic inflammation, neuroischemia, and increased expression of MMPs that degrade proteins, including growth factors.…”
mentioning
confidence: 99%
“…The pathogenesis of PEDs due to diabetic keratopathy may include both loss of epithelial migratory activity and an abnormal epithelial scaffold. We previously showed that FGLM-NH 2 + SSSR eyedrops [17] and PHSRN eyedrops [18] facilitated corneal epithelial migration in a rat model of diabetes. Furthermore, both types of eyedrops promoted corneal epithelial wound closure in patients with PEDs [12, 19, 20].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have previously shown that eyedrops containing the substance P-derived peptide FGLM-NH 2 plus IGF-1 [17] or PHSRN [18] facilitated corneal epithelial wound closure in diabetic rats. In addition to the effectiveness of PHSRN eyedrops for the treatment of PEDs in patients with diabetic keratopathy [12], we also found that eyedrops containing FGLM-NH 2 and either IGF-1 [19] or the IGF-1-derived peptide SSSR [20] were effective for the treatment of PEDs in patients with neurotrophic keratopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired neurogenic inflammation, due to diabetic neuropathy, contributes to enhanced susceptibility for diabetic foot ulcer. The neuropeptides known to be involved in impaired diabetic wound healing are substance P [99,211] and neuropeptide Y [100,212]. Further research is needed in order to evaluate the effect of the addition of neuropeptides to impaired wound healing and possibly consider this approach as a future therapy.…”
Section: Neuropeptidesmentioning
confidence: 99%